PSYCHOLOGICAL POSSIBILITIES OF FORMING INTERESTS IN VISUAL ARTS IN PRESCHOOL CHILDREN - Salakhidinova Kholida Haliljonovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the psychological aspects of the formation of motivs of visual art in preschool children are not the result of the random influence of the child’s personality and its psychological characteristics, but the formation of a certain concrete factor in the legal influence, the factors that have an important legal effect.